Unraveling the advantages of site-specific nutrient management in maize (Zea mays L.) for enhancing the growth and productivity under varied plant populations in the hot and moist sub-humid region of Odisha - Tadiboina, Gopala Krishna; Masina, Sairam; Chabolu, Venkata Raghava; Sagar, Maitra (Plant Science Today, 2024)
In developing countries like India, a cereal-based cropping system is one of the important practices, having a significant role in food security and the country’s economy. Among the cereal crops cultivated in India, maize is one among them having a huge market demand, and yield potential and can perform under various agroclimatic conditions. In the cultivation of cereal crops like maize, input optimization and intensification of farming by altering plant population are highly essential for agricultural sustainability as well as crop productivity. Nutrients can be efficiently applied through site site-specific approach by using a decision support system, namely, Nutrient Expert (NE) rather application of a recommended dose for an agroclimatic region. Considering the above fact, the research was carried out in the rabi season of 2022-2023 at the Post Graduate Research Farm ofCenturion University of Technology and Management (23?38' N latitude and 87?42' E longitude) in Odisha. The experiment was laid out in a split-plot design with different spacings and NE-based nutrient recommendations. The main factor consisted of 3 different spacings and 4 different nutrient recommendations were considered in sub-plots. The recommended dose of fertilizer for maize was 120-60-60 kg ha-1 of N: P2O5:K2O respectively. The results of the experiment revealed that the highest plant height (249 cm), dry matter accumulation (1556 g m-2), leaf area (5674 cm2 plant-1), grain yield (6362 kg ha-1), and stover yield (9334 kg ha-1) were obtained in 60 cm × 15 cm spacing. The NE-based nutrient management for a target yield for 10 t ha-1 recorded the highest values in terms of growth attributes, yield attributes, and yield of maize. The experiment concluded that providing fertilizers through NE-based nutrient recommendation for a target yield of 10 t ha-1 with a spacing of 60 cm × 15cm can be considered for obtaining better growth, yield attributes, and yield of maize.